Richards Building at 112-116 State Street, ca. 1890-1910 - Unknown (Tufts Archival Research Center, 2005)
Elevated view northwest of the Richards Building, located at 112-116 State Street between Merchants Row to the west-southwest and Catham Row to the east-northeast. 122 State Street is located to the east-northeast or to the right of the Richards Building. Signage and awnings adorn both buildings, which face southeast. Copyprint; Richards Building built, ca. 1867 9 1/2 x 6 7/8, 10 x 7 3/4 overall Photographs